Modeling and Optimization of Membrane Bioreactors and Moving Bed Biofilm Reactor‐Membrane Bioreactors. Issue 9 (26th July 2017) - Leyva-Díaz, Juan Carlos; Poyatos, José Manuel
Abstract: A membrane bioreactor (MBR) and two hybrid moving bed biofilm reactor‐membrane bioreactor systems (hybrid MBBR‐MBRs) were studied in terms of the process modeling and operation optimization through different mathematical models for organic matter and nitrogen removal. A multiple linear regression method and a multivariable statistical analysis were applied. The process variables were hydraulic retention time, total biomass concentration, temperature, chemical oxygen demand of the influent, and total nitrogen of the influent. In general, the values of the coefficient of determination ( R 2 ) for the different model fittings were higher for the hybrid MBBR‐MBR processes than those obtained for the MBR, which was probably attributable to the presence of suspended and attached biomass in the hybrid MBBR‐MBR systems. Abstract : Membrane bioreactors are becoming excellent alternatives for wastewater treatment, but further research into process modeling and optimization is needed. Here, mathematical models are described for organic matter and nitrogen removal and kinetic performance to allow optimization of a range of operational conditions for these systems.